EARLY FEEDING CHALLENGES AS BARRIERS TO CATCH-UP GROWTH IN LOW BIRTH WEIGHT INFANTS: A NARRATIVE REVIEW - Selma Avianty; Refani Alycia Kusuma; Hanna Audila (Journal of Indonesian Specialized Nutrition, 2026)
Background: Low birth weight (LBW) infants are highly vulnerable to postnatal growth failure due to physiological immaturity, increased metabolic demands, and feeding-related complications. Early feeding challenges may interfere with adequate nutritional intake during a critical period of growth and development, thereby impairing catch-up growth. Objective: This narrative review aimed to synthesize current evidence regarding early feeding challenges as barriers to catch-up growth in LBW infants. Methods: A narrative literature search was conducted using PubMed, Scopus, ScienceDirect, and Google Scholar databases. Relevant articles published between 2016 and 2026 were reviewed, focusing on feeding difficulties, nutritional management, and growth outcomes in LBW infants. Results: Early feeding challenges in LBW infants include impaired suck–swallow coordination, feeding intolerance, delayed enteral feeding progression, breastfeeding difficulties, and inadequate post-discharge feeding support. These factors may contribute to insufficient energy and protein intake, impaired nutrient utilization, and persistent growth faltering. Inadequate catch-up growth is associated with adverse neurodevelopmental, immunological, and metabolic outcomes. Conclusion: Early feeding challenges are major barriers to optimal catch-up growth in LBW infants. Comprehensive nutritional and multidisciplinary interventions are essential to support balanced postnatal growth and improve long-term health outcomes.